STUDY OF RESIDUAL RESOURCE AND ESTABLISHMENT OF THE LIMIT LIFE OF NON-PURCHASER PASSENGER CARS OF CONSTRUCTION OF KVZ (Transport systems and technologies, 2021)
In order to ensure the uninterrupted performance of passenger traffic, the task of ensuring the operation of rolling stock outside the extended service life, including passenger cars for the carriage of passengers, remains relevant. Based on this, there is a need for comprehensive research aimed at substantiating the possibility of ensuring operation while maintaining dynamic and strength characteristics. The article examines the residual life of load-bearing metal structures of passenger cars based on the results of technical diagnostics and standard tests. It is concluded that the condition of the load-bearing metal structures of passenger cars built by the Kryukiv Carriage Plant (KСP) after long operation does not approach the limit. The obtained practical and theoretical results make it possible to extend the service life of passenger cars for the construction of KCP beyond the factory set by 41 years.
Keywords: passenger carriage, bearing metal structures, control tests, residual life